Primary repair versus diversion in penetrating colon injuries - Alhamdani, Adil Karim; Albadri, Jasim M.; Abed, Husham J.; Abed, Hadeel. J. (AL-Kindy College Medical Journal, 2013)
Back ground: In Iraq, after 2003 had moreaccidents of the shell, bullet and stab abdominalwounds, more over colon injuries.Objective: The aim of this study is to evaluatethe most appropriate management of penetratingcolon injuries, comparing the primary repair withthe diversion.Methods: Eighty patient series with shell, bulletand stab colonic injuries during 4.5 years periodfrom June 2006-december 2010 at Al-Yarmoukteaching hospital. The study compared the use ofprimary repair versus diversion, analyzingvariables such as sex, age, severity of injury andmortality rate.Results: there were total 80 patients ,62 (77.5%)male and 18(22.5%) female .male :female ratio3.4:1. the most affected age group was 21-30years. 47 patients 58.75% were shell injuries.28patients 35% were bullet injuries. 5 patients6.25% were stab wounds. 46 patients 57.5%managed by primary repair ,one of them 1.25%died, while diversion in34patients 42.5%different grades of colon injuries ,5 of them6.25% died ,this was due to different factors suchas multiple organ injuries and post operativecomplications.Conclusion: the primary repair is safe andeffective regarding morbidity and mortality inthe management of grade II, III penetrating coloninjuries with minimal risk factors as compared todiversion.